2020
DOI: 10.3389/fonc.2020.551985
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing Assisted Laparoscopic Partial Nephrectomy vs. Conventional Nephrectomy in Patients With Complex Renal Tumor: A Systematic Review and Meta-Analysis

Abstract: The purpose of this meta-analysis was to systematically assess the influence of three-dimensional (3D) printing technology in laparoscopic partial nephrectomy (LPN) of complex renal tumors. Methods: A systematic literature review was performed in June 2020 using the Web of Science, PubMed, Embase, the Cochrane library, the China National Knowledge Infrastructure (CNKI), and the Wanfang Databases to identify relevant studies. The data relative to operation time, warm ischemic time, intraoperative blood loss, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Relevant studies have shown that 3D printing-assisted LPN can shorten the operation time and the warm ischemic time and reduce intraoperative blood loss. [23][24][25] These results are consistent with our study. However, these 3D printing models have not demonstrated the occurrence of APF.…”
Section: Discussionsupporting
confidence: 93%
“…Relevant studies have shown that 3D printing-assisted LPN can shorten the operation time and the warm ischemic time and reduce intraoperative blood loss. [23][24][25] These results are consistent with our study. However, these 3D printing models have not demonstrated the occurrence of APF.…”
Section: Discussionsupporting
confidence: 93%
“…Non-invasive devices are external applications, like 3DP models. The medical fields included are anesthesia [1], cardiology [2][3][4][5][6][7][8][9][10][11][12][13], coloproctology [14], dentistry [15][16][17][18], general surgery [19][20][21][22][23][24][25], health care engineering [26,27], hepatology [28], interventional radiology [29], medical education [30][31][32][33][34], neurosurgery [35][36][37][38][39], oncology [40][41][42][43] and radiation oncology [44][45][46]. Further medical fields included are oral and maxillofacial surgery [47][48][49]<...…”
Section: Non-invasive Applicationsmentioning
confidence: 99%
“…Further medical fields include plastic surgery [93,94], traumatology [95][96][97], urology [98][99][100][101][102] and vascular surgery [103][104][105][106]. The affected organs or organ systems include the aorta [13,103,106], bladder [29], brain [35,37,39], cranium [30, 31, 34, 36, 44, 48-50, 53-55, 82, 84, 86, 91], ear [48, 78-81, 83, 93], female internal genitals [46], heart [2-12, 87, 88, 104], jaw [17, 20, 21, 23, 25, 47-52, 55, 56], kidney [29,41,98,[100][101][102], lip [94], liver [19,22,28], musculoskeletal system [20, 21, 24, 31-33, 38, 43, 57-77, 89, 90, 92, 93, 95-97], prostate [98,99], rectum and colon [14,40,42,45], spine [38,59,68,77,…”
Section: Non-invasive Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D-printed models were welcomed during the performance of complex and high-precision surgeries ( Figures 1D,E ). The advantages of the 3D kidney for partial nephrectomy (PN) include shorter operation times and warm ischemia times, less intraoperative blood loss, as well as fewer complications, in comparison to PN with imaging alone ( 9 ). Our previous data revealed that, compared with traditional laparoscopic partial nephrectomy, 3D-printed models can help to reduce the warm ischemia time and the estimated intraoperative blood loss from 29.2 to 24.6 min, and 131.1 ml to 118.7 ml, respectively, in patients with complex renal tumor (R.E.N.A.L score>8) ( 8 ).…”
Section: D Printing In Renal Cancermentioning
confidence: 99%